Comparative Analysis of Blended Learning and Conventional Methods in Enhancing the Achievement of Pre-Service Secondary Teachers in Inclusive Education - Nirola, Bhabani; Kumar Barik, Prasanta; Naik, Chakradhar (Journal of Neonatal Surgery, 2025)
This study is about how the Blended Learning Approach affects the achievement of pre-service secondary teacher’s performance when it tries to study on Inclusion in Education. The main aim of this study is to focus how the Blended Learning Group and the Conventional Method Group perform on a test after they have been taught. The Blended Learning Group (BLG) (taught through Blended Learning Approach) is being compared to the Conventional Method Group (CMG) (taught through Conventional Method). For this experimental study criterion test was used to study the post-test effect. The sample of the study determine by dividing equally through adjusting mean scores of an intelligence test upon the students. The main aim of the study was to examine whether there is a significant difference in the performance of these two groups. The findings of the study revealed that the Pre-Service Secondary Teachers in the Blended Learning Group and the Conventional Method Group differed significantly....